The Role of Talent Management in Promoting Organizational Agility Empirical Study from the Governmental Sector in the United Arab Emirates: A Conceptual Framework - Tamadher Aldabbagh (Philippine Association of Institutions for Research, Inc., 2023)
The research redefined, summarized, categorized, and expanded the current conceptual understanding of the effect of talent management dimensions on organizational agility in the governmental sector in the UAE. The study conceptualizes the relationship between all studied constructs, which enriches the current knowledge for that specific topic. The main contribution of this research is that it is the first attempt to provide a more comprehensive explanation, and scattered literature covers the theories linking broader academic links on how talent management promotes agility through its processes (Recruitment and selection - Competence training - Development -Performance management). All affect its components (Strategic orientation towards agility - Agile organizational structures, methods, and process - Agile organizational culture - Facilities supporting agility). Moreover, it is suggested that future research may examine other talent management constructs to reflect a deep understanding of the construct's effect on organizational agility from different perspectives. One of the recommendations for future research is to determine the causal effect between variables by conducting empirical evidence through surveys and correlational analysis of the obtained data.